DESCRIPTION OF THE TECHNOLOGICAL PROCESS BIOLOGICALLY ACTIVE FOOD SUPPLEMENTS (BAA) "LIK" VEGETABLE OILS (Eureka Journal of Health Sciences & Medical Innovation, 2026)
This technological instruction applies to biologically active food supplements (BAA) “LIK” vegetable oils, produced from oils obtained by cold pressing, preserving the nutritional and biological value, released in soft gelatin capsule form, intended for sale through special sections of grocery stores and over-the-counter sections of pharmacies as a biologically active food supplement (hereinafter referred to as BAA).